The fifth column [compact disc, unabridged] - Gross, Andrew, 1952- (Macmillan Audio, 2019)
February 1939. Europe teeters on the brink of war. In New York City, twenty-two thousand cheering Nazi supporters pack Madison Square Garden for a raucous, hate-filled rally. In a Hell's Kitchen bar, Charles Mossman is reeling from the loss of his job and the demise of his marriage when a group draped in Nazi flags barges in. Drunk, Charlie takes a swing at one with tragic results and a torrent of unintended consequences follows. Two years later, Charles's estranged wife and six-year-old daughter, Emma, now live in a quiet brownstone in a German-speaking New York City neighborhood, where support for Hitler is open. Charles, just out of prison, struggles to put his life back together, while across the hall from his family, a kindly Swiss couple, Trudi and Willi Bauer, have taken a liking to Emma. But Charles begins to suspect that they might not be who they say they are.